“I Am Not My Bodies:” Transgender Embodiment in Nina Arsenault’s The Silicone Diaries - White, Zaren Healey (Atlantis, 2016)
This article examines transgender embodiment through analysis of Canadian transgender performance artist Nina Arsenault and her autobiographical play The Silicone Diaries (2012b). I discuss Arsenault’s life writing, plays, and self-portraiture to explore how her pursuit of an exaggerated ideal of beauty simultaneously subverts essentialist notions of what it means to be a woman.This paper was awarded the second prize in the Women’s and Gender Studies et Recherches Féministes (WGSRF) Graduate Essay Prize competition in 2014.